Proteolytic Surface-Shaving and Serotype-Dependent Expression of SPI-1 Invasion Proteins in Salmonella enterica Subspecies enterica - Fagerquist, Clifton K.; Zaragoza, William J. (Frontiers in Nutrition, 2018)
We performed proteolytic surface-shaving with trypsin on three strains/sevovars of Salmonella enterica enterica (SEE): Newport, Kentucky and Thompson. Surfaced-exposed proteins of live bacterial cells were digested for fifteen minutes. A separate twenty hour re-digestion was also performed on the supernatant of each shaving experiment to more completely digest protein fragments into detectable peptides for proteomic analysis by nano-liquid chromatography-electrospray ionization-Orbitrap mass spectrometry. Control samples (i.e. no trypsin during surface-shaving step) were also performed in parallel. We detected peptides of flagella proteins: FliC (filament), FliD (cap) and FlgL (hook-filament junction) as well as peptides of FlgM (anti-28 factor), i.e. the negative regulator of flagella synthesis. For SEE Newport and Thompson, we detected Salmonella pathogenicity island 1 (SPI-1) secreted effector/invasion proteins: SipA, SipB, SipC and SipD, whereas no Sip proteins were detected in control samples. No Sip proteins were detected for SEE Kentucky (or its control) although sip genes were confirmed to be present. Our results may suggest a biological response (< 15 minutes) to proteolysis of live cells for these SEE strains and, in the case of Newport and Thompson, a possible invasion response.